Improving Reading in Adolescents and Adults With High-Functioning Autism Through an Assistive Technology Tool: A Cross-Over Multinational Study - Cerga-Pashoja, Arlinda; Gaete, Jorge; Shishkova, Antoneta; Jordanova, Vesna (Frontiers in Psychiatry, 2019)
People with autism spectrum disorder (ASD) experience reading comprehension difficulties, often misinterpreting complex texts, metaphors and idioms. We have developed and tested a new assistive technology tool for adaptive, personalised text simplification, called Open Book. This tool is an open-sourced, online platform, that uses Natural Language Processing with the specific aim of assisting reading and aiding understanding of written text for people with ASD. The accessibility and effectiveness of Open Book was tested by examining the differences in text comprehension scores between the original texts and texts that were simplified by Open Book tool, randomly allocated to study participants. Two hundred and forty-three participants (153 adults and 90 adolescents) with high-functioning ASD were recruited in the UK, Spain and Bulgaria. Regarding the primary outcome, results showed that both adults and adolescents with ASD gave more correct answers for the simplified (M=11.2, SD=4.1) than original texts (M=10, SD=4.; p<0.001). This finding was consistent across age-groups and countries. Regarding the secondary outcome, when participants were asked to blindly rate how easy was to understand each text, simplified texts were rated as easier (M=7.6, SD=2.4) to understand than the original texts (M=8.7, SD=2.6; p<0.001). The Open Book software seems to have the potential to be a useful tool in assisting reading among people with ASD. Our findings support our primary hypothesis that texts simplified through Open Book were easier to comprehend compared to original texts.